Lucille Kerr & Alejandro Herrero-Olaizola (eds.), Teaching the Latin American Boom. The Modern Language Association of America, New York, 2015; 297 pp. (Options for Teaching, 37). - Celis Mendoza, Martha (El Colegio de México, 2017)
Se reseñó el libro: Teaching the Latin American Boom.